Quantifying Long-Term Bird Population Responses to Simulated Harvest Plans and Cumulative Effects of Disturbance - Leston, Lionel; Bayne, Erin; Dzus, Elston; Sólymos, Péter; Moore, Tom; Andison, David; Cheyne, Dave; Carlson, Matt (Frontiers in Ecology and Evolution, 2020)
There is interest in linking outputs from land use simulators to bird species distribution models to project how boreal birds will respond to cumulative effects of caribou (Rangifer tarandus) conservation, harvest, fire, and energy-sector development in Alberta. Our hypotheses were: 1) species associated with older mixed-wood stands would decline more if harvest was shifted away from areas used by caribou to areas with more mixed-wood; and 2) species associated with older forests would be more negatively affected by the combined effects of harvest, fire, and non-forestry footprint than by harvest alone. We used vegetation data from two harvest scenarios produced in Patchworks as inputs for density models of 20 boreal forest songbird and woodpecker species in Alberta. We projected abundance of these species over 50 years under: 1) two scenarios created in Patchworks, without fire but with and without deferral of timber harvest within a caribou conservation zone on lands tenured to Alberta-Pacific Forest Industries Inc.; 2) a scenario with fire but no human footprint; and 3) five scenarios in ALCES Online, in which habitat was affected by Patchworks harvest locations, fire (1-2 × current rate), and energy sector development (present or absent; with or without seismic line reclamation to improve caribou habitat). In the Patchworks scenarios, we found similar projected numbers of each bird species over time, whether harvest deferral occurred or not. Both harvest plans increased habitat and numbers for most species associated with older forests over 50 years, while most species associated with younger forests declined in both harvest plans, because average projected forest age increased over 50 years. Fire and other footprint generally reduced relative amount of habitat for species associated with older forests, which still increased over time, while other species responded positively or less negatively to fire. Seismic restoration created habitat for three-quarters of species that responded negatively to energy sector development over 50 years. As projections depended on whether just harvest, fire or all footprints were analyzed, multiple human impacts over time beyond harvest should be considered in conservation and land use planning based on long-term predictions about wildlife in anthropogenic landscapes.